2021
DOI: 10.18510/hssr.2021.9221
|View full text |Cite
|
Sign up to set email alerts
|

A Nexus Between Household Characteristics and Women’s Empowerment: A Case Study of Punjab, Pakistan

Abstract: Purpose of the study: The empowerment of women is an important aim for them to be fully engaged in economic life and to achieve sustainable growth worldwide. One form of empowerment is to provide women with basic facilities. Methodology: The study also analyzed the impact on women's empowerment by primary data taken via multi-phase cluster sampling methods of household socio-economic and cultural characteristics in Punjab. Given the diversity of nature and context, the 6-dimensional empirical polychoric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, the correlation analysis in of the study refers to the results of research by Batool (2018) and Eastwick et al (2006), which similarly highlight the positive correlation between education and women's empowerment in mate selection. The robust correlation coefficient and significant value of p substantiate the reliability of this relationship.…”
Section: Quantitative Discussionmentioning
confidence: 96%
“…Moreover, the correlation analysis in of the study refers to the results of research by Batool (2018) and Eastwick et al (2006), which similarly highlight the positive correlation between education and women's empowerment in mate selection. The robust correlation coefficient and significant value of p substantiate the reliability of this relationship.…”
Section: Quantitative Discussionmentioning
confidence: 96%
“…Many studies explored several socio-economic, personal and household factors that impact the empowerment level of women in a family. Hafsah et al (2021) demonstrated that the position of women, care of legitimate privileges, clinical access and political investment positively affected women's empowerment. Khan et al (2021) found that women with education and employment are more empowered to make decisions regarding expenditure and travelling in the family; however, women with less education and from jointly structured families are less empowered.…”
Section: Factors Affecting Women's Empowermentmentioning
confidence: 99%
“…Pumar (2021) stated that improving access to education, addressing social attitudes, and advocating for gender equality in educational opportunities and outcomes are just a few of the many strategies needed to address these discrepancies. Batool et al (2021c) stated that gender disparities can only be eliminated if females are provided with equal opportunities in decision-making and jobs. Batool et al (2021c) concluded that for sustainable economic development, it is important that females in rural areas also provide digital literacy females should know how to use technology and have access to the internet at low prices.…”
Section: Introductionmentioning
confidence: 99%
“…Batool et al (2021c) stated that gender disparities can only be eliminated if females are provided with equal opportunities in decision-making and jobs. Batool et al (2021c) concluded that for sustainable economic development, it is important that females in rural areas also provide digital literacy females should know how to use technology and have access to the internet at low prices. Chidi ( 2021) stated there are a number of reasons why there are gender differences in educational achievement, such as poverty, societal biases, cultural standards, and resource limitations.…”
Section: Introductionmentioning
confidence: 99%